Clinical Interpretation of Urinalysis for Early Detection of Kidney Disorders: A Narrative Review - Adinda Puspita Dewi; Selfie Selfie; Baety Adhayati; Yuda Nabella Prameswari; Lola Febriana Dewi; Luluk Hermawati (International Journal of Cell and Biomedical Science, 2025)
Background: Chronic kidney disease (CKD) is a global health issue with a steadily increasing prevalence and often remains asymptomatic in its early stages. This silent progression contributes to delayed diagnosis and limited therapeutic options. Urinalysis is a simple, inexpensive, and noninvasive examination that remains relevant as an early screening tool to detect renal abnormalities before clinical manifestations appear. Methods: This narrative review summarizes the latest scientific evidence regarding the diagnostic value of urinalysis in the early detection of kidney disorders by highlighting the physical, chemical, and microscopic parameters of urine. Literature searches were conducted using PubMed, Scopus, and Google Scholar databases for studies published between 2020 and 2025 with the keywords urinalysis, kidney disease, early detection, uACR, and eGFR. Only English- or Indonesian-language articles relevant to the topic and containing empirical data were included. Results: Urinalysis has been shown to provide early indicators of proteinuria, hematuria, and pathological casts that reflect glomerular and tubular injury. Integration of urinalysis results with uACR and eGFR measurements, as recommended by KDIGO 2024, improves diagnostic accuracy and risk stratification. Additionally, automated digital microscopy and emerging biomarkers such as NGAL and KIM-1 show substantial potential in strengthening early detection capabilities. Discussion and Clinical Implications: Urinalysis not only serves as a screening tool but also holds prognostic value in guiding follow-up and clinical management of high-risk individuals. Proper interpretation of urinalysis findings can assist clinicians in determining the need for further assessment, initiating earlier interventions, and optimizing prevention of CKD progression. Conclusion: Urinalysis remains an essential basic examination for the early detection of kidney impairment. Its integrated application with modern laboratory parameters can enhance diagnostic effectiveness, accelerate clinical intervention, and reduce the global burden of chronic kidney disease.